Successful twin pregnancy in a common variable immunodeficiency patient: Case study and clinical insights (Indian Journal of Case Reports, 2026)
Common variable immunodeficiency (CVID) is a primary immunodeficiency characterized by an increased vulnerability to recurrent respiratory and gastrointestinal infections, as evidenced by low immunoglobulin levels. Pregnancies in individuals diagnosed with CVID are classified as high-risk due to the considerable variability in disease presentation and potential complications that may arise. Principal concerns during pregnancy associated with CVID include infections, preterm labor, postpartum hemorrhage, thrombocytopenia, and a heightened incidence of eclampsia and pre-eclampsia. We provide a detailed overview of our clinical experience in managing pregnancy for a patient with CVID of a 30-yearold primigravida diagnosed with CVID at 17 weeks of gestation with a twin pregnancy. Implementing targeted care strategies in tertiary healthcare settings is expected to enhance pregnancy outcomes for women diagnosed with CVID.